Mouse hippocampal phosphorylation footprint induced by generalized seizures: Focus on ERK, mTORC1 and Akt/GSK-3 pathways. (17th December 2015) - Gangarossa, Giuseppe; Sakkaki, Sophie; Lory, Philippe; Valjent, Emmanuel
Highlights: MES induces biphasic regulation of ERK1/2. MES induces biphasic modulation of mTORC1. MES regulates the Akt/GSK-3 pathway. MES induces plasticity-associated immediate early genes. Common molecular footprint for epileptic hippocampus. Abstract: Exacerbated hippocampal activity has been associated to critical modifications of the intracellular signaling pathways. We have investigated rapid hippocampal adaptive responses induced by maximal electroshock seizure (MES). Here, we demonstrate that abnormal and exacerbated hippocampal activity induced by MES triggers specific and temporally distinct patterns of phosphorylation of extracellular signal-related kinase (ERK), mammalian target of rapamycin complex (mTORC) and Akt/glycogen synthase kinase-3 (Akt/GSK-3) pathways in the mouse hippocampus. While the ERK pathway is transiently activated, the mTORC1 cascade follows a rapid inhibition followed by a transient activation. This rebound of mTORC1 activity leads to the selective phosphorylation of p70S6K, which is accompanied by an enhanced phosphorylation of the ribosomal subunit S6. In contrast, the Akt/GSK-3 pathway is weakly altered. Finally, MES triggers a rapid upregulation of several plasticity-associated genes as a consequence exacerbated hippocampal activity. The results reported in the present study are reminiscent of the one observed in other models of generalized seizures, thus defining a common molecular footprint induced by intense and aberrant hippocampal activities.